Purim and Sukkot Rituals in Depok: Negotiation of Jewish Community in Indonesia - Zuchra Zuchra; Edi Dwi Riyanto (Universitas Airlangga, 2023)
Judaism as a nation and as a religious community are two different but interrelated things. In the Jewish Diaspora, some Jews entered Indonesia along with the entry of Dutch and Portuguese colonialism. Due to different conditions from those with established institutions in other countries, Jews in Indonesia, especially in Jakarta and Depok carry out their religious traditions differently because they adapt to the environment in which they live, where the majority are Muslims. Thus, the tradition carried out by them is local and adapts carefully to the environment. This research using descriptive qualitative method shows that negotiation is a way of surviving for the Jews in the Depok area. The celebration of Purim as a reminder of the survivors of persecution from the Persians, and Sukkot as a reminder of the temporary residence of the Jews, were also carried out under conditions that also adjusted, so a strategy was needed. In addition to the results of the research above, adjustments were also made using local materials to keep them in accordance with their religious laws but obtained in the area where they live.